Notes on Lagi-Lagitya relations in Jumla - Gurung, Om (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v8i0.1118 Occasional Papers in Sociology and Anthropology Vol.8 2003 p.12-17